2014
DOI: 10.15740/has/tajh/9.2/416-420
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic nutrients on growth, flowering and yield of Gladiolus grandiflorus L.

Abstract: : The present study was laid out in RBD with three replications. Various organic fertilizers viz., farm yard manure (FYM) @ 7.5 t ha -1 , leaf mould compost @ 7.5 t ha -1 , vermicompost (VC) @ 2.5 t ha -1 , humic acid (HA) @ 0.2 per cent (FS), VAM and inorganic fertilizer (RDF 100:50:150 NPK kg ha -1 ) were applied. The growth and yield parameters were studied at different stages of crop growth. The study revealed that the growth characters viz., plant height, at 30 and 45 DAP, number of leaves, leaf length, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 0 publications
8
5
0
Order By: Relevance
“…Among the three compost treatments, the high level treatment (7.5 ton/fed) resulted the highest values for all corm and cormels production over both low and medium compost treatments in the two seasons. Similar results were also revealed on gladiolus plants by Ruppenthal and Castro (2005), Chandar et al (2012), Pradeep et al (2014) Sankari et al (2015, Hassan (2016) and Khanam et al (2017).…”
Section: Resultssupporting
confidence: 78%
“…Among the three compost treatments, the high level treatment (7.5 ton/fed) resulted the highest values for all corm and cormels production over both low and medium compost treatments in the two seasons. Similar results were also revealed on gladiolus plants by Ruppenthal and Castro (2005), Chandar et al (2012), Pradeep et al (2014) Sankari et al (2015, Hassan (2016) and Khanam et al (2017).…”
Section: Resultssupporting
confidence: 78%
“…These results are in close agreement with those obtained by Khan et al (2002); Dongardive et al (2007); Ahmed et al (2013), Pandey et al (2013), Pradeep et al (2014), Pereira et al (2016) and Abdel-Mola (2017) on gladiolus.…”
Section: Flowering Parameterssupporting
confidence: 92%
“…These results are in parallel with those of Mazhar et al (2012) who studied the effect of four concentrations of humic acid (0, 1, 1.5 and 2%) used as a foliar spray on flower parameters of chrysanthemum plant and found that humic acid (2%) gave a significant increase in flower number. Also these results are in harmony with those obtained by Pradeep et al (2014) on gladiolus, and Palanisamy et al (2015) on gerbera plants. Also these results are in harmony with those obtained by (Attoa, 2008 ;Deljou and Gholipour, 2014) who studied the effect of calcium spray on flower characters of gerbera plants.…”
Section: Effects Of Humic Acid and Calcium On Number Of Flowers Flowsupporting
confidence: 91%